(untitled) (Sociologisk Forskning, 2003)
In this article career as metaphor and various career models are the object of a critical review. The question at issue is whether career as metaphor helps us understand the social dynamics that characterize substance abuse? Different career models such as the stepping-stone and gateway hypothesis and H S Beckerscareer model are scrutinized. It is pointed out that these career models are one-sided and have serious limitations, since they leave out important variables pertaining to class, gender, ethnicity, politics and culture. In order to create a credible representation of the development of drug abuse the different levels and dimensions of social reality must be described. Despite the extensive critique that has been passed on the concept of drug abuse as career it is still widely used by professionals as well as laymen. This fact of the matter is discussed and the author argues that the concept of drug abuse as career serves important functions in the government of drug abuse. Besides being an important instrument in drug treatment the concept of drug abuse as career is used in order to give legitimacy to the political control of drugs. From that perspective the concept drug abuse as career can be understood as a narrative serving important functions in the social control of untoward behavior.